Poetic Peripheries - Sarantou, Melanie; Miettinen, Satu; Mäkiranta, Mari; Kontio, Taina (2019)
The Poetic Peripheries exhibition (Vivienne Crisp Gallery) includes artists Taina Kontio, Satu Miettinen, Mari Mäkiranta and Melanie Sarantou. This collective includes four researcher-artists who focus on the questions of social responsibility, arctic nature, global and local peripheries and cultural identities, which are visualised through images of arctic waters, landscapes and people. The exhibition was set up by Port Pirie Regional Gallery and it represents the outcomes of artistic research that focuses on the development of artistic expression, methodologies and societal dialogue, thus interweaving the exhibitions, artistic work, research strategies and societal challenges that the researchers address. The Poetic Peripheries exhibitions discusses meanings related to gender and space through art video, photography and fashion. The art work is about changing identities, the relationships between human and nature, and connotations and relationships with safe spaces.